1638b The food choice at work trial: from evaluation to commercialisation and practical application in everyday workplace settings. (24th April 2018) - Geaney, F
Abstract : Introduction: The surrounding environments in which individuals live and work influences their health behaviours. Macro and micro-level modification of these environments is an important catalyst for behaviour change. However, evidence on effective workplace dietary interventions is limited. The FCW trial assessed the comparative effectiveness of a workplace dietary intervention involving nutrition education and system-level dietary modification both alone and in combination versus a control workplace on employees' dietary intakes, nutrition knowledge and health status. An economic evaluation assessed the cost-effectiveness of the FCW intervention from the perspective of healthcare providers in terms of QALYs and employers in terms of monetary benefits (reduced absenteeism). Methods: Four manufacturing workplaces in Ireland were allocated to control, nutrition education (Education), system-level dietary modification (System-level) and nutrition education and system-level dietary modification (Combined). Nutrition education included group presentations, individual consultations and detailed nutrition information. System-level dietary modification included menu modification, fruit price discounts, strategic positioning of healthier alternatives and portion size control. Data on dietary intakes, nutrition knowledge, health status, QALYs and absenteeism were obtained at baseline and at 7–9 months follow-up. Multivariate analysis of covariance compared changes across the groups. The economic evaluation included cost-utility and cost-benefit analyses. Results: Follow-up data were obtained for 541 employees (18–64 years) (64% of 850 recruited). There were significant positive changes in intakes of saturated fat (p=0.013), salt (p=0.010) and nutrition knowledge (p=0.034) between baseline and follow-up in the combined intervention versus the control. Significant changes in BMI (− 1.2 kg/m 2 (p=0.047) were also observed in the combined intervention. System-level modification yielded the highest additional QALYs (€101.37/QALY) and annual net benefit for employers (€56.56/employee). Discussion: Combining nutrition education and system-level dietary modification is an effective approach for promoting healthy eating at work. The FCW intervention is a sustainable cost-effective model and wide-scale implementation is underway at local and national workplaces.